Augmented Reality Technology for the Introduction of Mobile-Based Spaces with the Hough Transform Method (Case Study: Akprind Institute of Science and Technology Campus Locations) - Galuh Ayu Novilia; Uning Lestari (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
AKPRIND Institute of Science & Technology (IST AKPRIND) Yogyakarta is one of the private universities in Yogyakarta which has 3 different building locations so that it has many rooms and buildings in a large area. In addition, the shape of the room is similar and the lack of information and the location of the campus which is divided into three, often makes it difficult for new students to find a room to carry out the lecture process later. Augmented Reality (AR) is a concept of combining virtual reality with world reality (real life), so that 2-dimensional (2D) or 3-dimensional (3D) virtual objects seem to look real and blend into the real world. The AR camera will capture and identify markers and then position and place a virtual data object on the marker. In the process of creating an AR application, Unity3D tools and a database using Vuforia are required. The results of the application will be tested using the Standard Hough Transform (SHT) method. SHT is tested to get a conclusion about the detection distance value at the distance between the image and the camera. The test was carried out using 3 marker sizes with a tilt angle of 0 °, 15 °, 30 °, 45 °, 60 °, 75 °, and 90 ° carried out with 20 watts of lamp lighting and a distance of 2.5 meters between the lamp and the marker. Based on testing with the SHT method, the larger the marker size, the farther the marker distance can be detected.